Evaluation of Bulbocaverneus Reflex (Bcr) in The Erectile Dysfunction - Ardıçoğlu, Arslan; Yoldaş, Tahir; Yüzgeç, Veysel; Tuygun, Uğur (Fırat University, 2003)
Aim: The purpose of this study is to determine the etiology of neurojenic impotence and bulbocavernosus reflex latency (BCR- L) in the erectil dysfunction. Materials and method: For this study 32 male patient were participated ,who attended andrology clinic, aged between 25- 61 in the between March 2002 and November 2002 patients. All the participant were in good health and any patient that had metobolic disorder, pelvic trauma and operation were excluded from study. All the cases were evaluated in the base of blood biochemistry rutin urine test, papaverin injection, penil colorful doppler USG and BCR latans. Results: 12 (37,5%) patients with psicojenic impotance, 3 (9,4%) patients arterial failure, 2 (6,25%) patients with venous leak,1 (3,1%) patient with hormonal deficiency (testestore) and 3 (9,4%) patients with patients long latency were out of 32 patients. Based on their etiologic evaluation, no particular reason was present in the 11 (34.4%) patients out 32. These patients were fallowed by both psychiatric and andrology clinic. Conclusion: Evaluation of BCR latency might be useful in the neurogenic impotence in the ED cases.

Amaç: Erektil disfonksiyon (ED)'lu olgularda nörojenik impotansın ayırıcı tanısında, bulbo kavernözal refleks latans (BCR-L)'ın etyolojideki etkinliğini belirlemek. Gereç ve yöntem: Mart 2002 ile Kasım 2002 tarihleri arasında androloji polikliniğimize ED şikayetiyle başvuran 25 ile 61 yıl (ortalama 42,6 ± 11,5) 32 erkek hasta çalışmaya alındı. Metabolik bozukluğu olan, pelvik travma ve cerrahi geçiren hastalar çalışma dışı bırakıldı. Olgular kan biyokimyası, rutin idrar tetkiki, papaverin enjeksion testi, penil renkli dopler ultrasonografi ve BCR latans testi ile değerlendirildiler. Bulgular: 32 hastanın 12'sinde (%37,5) psikojenik impotans, 3'ünde (%9,4) arteryal yetmezlik, 2'sinde (%6,25) venöz kaçak, birinde (%3,1) hormonal defisit (testesteron) ve 3 hasta da (%9,4) BCR latans uzamış olarak tespit edildi (40 ms ve üzerinde). 11 hastada (%34,4) etyolojik değerlendirmeler sonucunda hiçbir neden belirlenemedi. Bu hastaların takipleri psikiatri kliniği ile birlikte sürdürülmektedir. Sonuç : BCR latans değerlendirilmesi etyolojisi araştırılan ED'li olgularda nörolojik impotansın ayırıcı tanısında yardımcı bir test olarak kullanılabilir.
Erektil Disfonksiyonda Bulbokavernöz Refleks (Bcr)'in Değerlendirilmesi